COMPARATIVE ANALYSIS OF CRYPTOCURRENCIES VERSUS FIAT MONEY - Georgiana Iulia LAZEA; Ovidiu Constantin BUNGET; Anca Diana SUMĂNARU (Annals of the University of Oradea: Economic Science)
This article aims to provide a comparative analysis of cryptocurrencies and fiat money, in the context in which the former might be considered an alternative to the latter. Mainly, we perform a literature review and qualitative analysis of 64 articles from Web of Science Core Collection, published between 2017 and 2023, using as keywords “cryptocurrencies” and “fiat money”. The information processing methodology involved presenting the data and information concisely, in order to gain a point of view on how crypto assets can be perceived in comparison with other financial assets. The results present the authors' conclusions regarding the economic differences and similarities between cryptocurrencies and traditional money. It also includes the limitations of the research and offers future directions for study.